A Review on Medicinal chemistry of Sarbocalm - Kush, Luv; Sharma, Nitin (Asian Journal of Pharmaceutical Research and Development, 2019)
Sarbocalm is recently marketed broad spectrum analgesic formulation of ayurvedic nature. The clinical merit of this was elucidated by structural plausibility and rationality of mechanism through non-ayurvedic approach.